Buta Mata dan Buta Hati: Strategi Pastoral Yesus Kristus Dalam Markus 8:22-26 - Adilang, Ryanto (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2024)
Love is the foundation for theology but also for doing our duties and responsibilities as Christians. Love is also what moved Jesus to pass on the responsibility of shepherding to the apostles, then later became a mandate for the Church today. Thus, love will always be the main weapon in the Church's efforts to enact Pastoral Counseling. But the next question is, how will love be the answer to today's pastoral challenges? This question needs an answer because pastoral challenges have transformed into more complicated ones. The researcher determined a qualitative research method with a descriptive approach as the method to be used to explore the research problem. To analyze the text of Mark 8:22-26, the hermeneutic method of historical criticism is deemed suitable to exegete the text and then present new meanings in the context of the Church today. This research is expected to provide constructive results for the ministry of Pastoral Counseling in Churches, but also in terms of scientific development of Pastoral Counseling in Christian Theological Universities. In addition, the results of this research will also provide renewal strategies in Pastoral Counseling services for the Church so that these services run well and effectively.